Self Organzied Wireless Sensor Network Model for Military Decentralized Applications - Manivannan, T (International Journal of Computer Sciences and Engineering, 2025)
Developments in integrated circuit design technology are expected to make the mass production of sensor devices relatively inexpensive, and hence such large sensor networks are likely to be common.A cluster-based scheme is proposed as a solution for this problem. The proposed scheme extends First Input High Energy (FIHE) clustering algorithm and enables multi-hop transmissions among the clusters by incorporating the selection of cooperative sending and receiving nodes. We propose a sensor network architecture based on the cluster-tree based multi-hop model with optimized cluster head election and the corresponding node design method to meet the tactical requirements. In the earlier system, such types of networks for transmission of information are available but there is no security mechanisms for providing the security for that transmitted information. Because several attackers may enter into the network without any authentication and they can attack the network and they can access the data or service they require. With the proposed WSN architecture, one can easily design the sensor network for military usage in remote large scale environments